Historical Prophetic Sunnah Between Supporters And Deniers - Al Khalaf, Abdul Aziz Muhammad (Journal of Islamic and Religious Studies, 2020)
A group of contemporary rationalists have repeatedly maintained that the rulings derived from the Sunnah have a historical framework that does not transcend them. After being proved, they must remain locked in the time in which they were said, and we are not obliged to follow them. The prophetic interpretation of the Qur'anic text is not the only interpretation, Is one possible form of interpretation. The rationalists market some evidence of this, including: copies, reasons for descent and causes of roses, and the language of some Koranic verses. In this research we will discuss the issue of this issue, and the statements of the parties and their evidence.